Quantitative PCR approach to SNP detection and linkage mapping in Caenorhabditis elegans - Christopher A. Shelton (BioTechniques, 2006)
I report a method for single nucleotide polymorphism (SNP) detection and linkage mapping in Caenorhabditis elegans using automated oligonucleotide design and fluorescence-based quantitative PCR detection. Nine hundred twenty-three oligonucleotide pairs were designed to produce small products of <150 bp for efficient amplification in a PCR, with one oligonucleotide of each pair overlapping a SNP site at the 3′ -most nucleotide. A subset of the pairs were tested, and efficient allelic discrimination was obtained for SNPs between N2, the canonical laboratory strain, and CB4856, a strain isolated from Hawaii commonly used for mapping studies. Linkage mapping is demonstrated using the unc-119 locus of C. elegans This quantitative PCR method provides an inexpensive, uniform, and automatable detection alternative for genetic mapping strategies in C. elegans or other organisms.